Geodynamic development of the lithosphere of Ukraine and its role in the formation and location of mineral deposits - V. I. Starostenko; O.B. Gintov; R. I. Kutas (Геофизический журнал, 2011)
Comprehensive studies of the lithosphere structure of Ukraine have been performed lately at the Institute of Geophysics NASU in connection with solving the problems of prospecting, diamonds and oil. These studies included: comprehensive analysis of geological-geophysical data on tectonics and deep structure of the Earth's crust and upper mantle; plotting the complex three-dimensional geophysical and geodynamic model of lithosphere; generalization of global experience in application of geophysical, including tectonophysical, methods for the search and prospecting of different kinds of mineral deposits. The results of studies allow drawing some conclusions on the character of geodynamic processes, having an influence on formation and location of deposits in the territory of Ukraine.